Governance, Business and The Environment - Maliah Sulaiman (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Traditionally, discussions on corporate governance (CG) have largely focused on economic sustainability.This is not surprising as CG issues have largely arisen out of accounting irregularities uncovered atprominent organizations, such as Enron, Tyco and WorldCom, and various other well-known companies.The focus of CG now, however, is broader….besides profits, companies are also focusing on the “people”and the “planet” too. Thus, the emphasis of CG today is on both the economic and environmentalsustainability. Given this, boards cannot be lackadaisical about social and environmental issues. How cancompanies achieve this? According to the Coalition for Environmentally Responsible Economies(CERES) in its CERES Roadmap for Sustainability”, a sustainable company is one that has the necessarygovernance structures in place, extensive stakeholder engagement undertaken and the standards and scopeof public disclosure and transparency instituted. Essentially, the Roadmap contains 20 specificexpectations for corporate performance that are categorised into 4 main perspectives: governance,stakeholder engagement, disclosure and performance. Thus, companies should embed sustainabilityissues in management and board structures, goal-setting and strategic decision-making and engage inrobust dialogue with stakeholders across the whole value chain. Additionally, companies shouldregularly report on sustainability strategies and performance. Disclosure will include credible,standardized, independently verified metrics encompassing all material stakeholder concerns, and detailedgoals and plans for future action. Further, a sustainable company is one that embarks on achievingreductions in carbon emission and water use, procurement of renewable energy, improved energyefficiency and having a supply chain that meets high environmental and social standards. Moreimportantly, companies are increasingly aware that a large part of their output consists of material waste(or non-product output). In particular, material flow cost accounting (MFCA), an environmentalmanagement accounting (EMA) tool that has now become an international standard, ISO 14051, can helpcompanies address environmental issues as well as improve their bottom lines. Finally, to be proactive onenvironmental issues companies must understand and manage its environmental costs; introduce wasteminimization schemes; understand and manage lifecycle costs; measure its environmental performanceand embark on a strategic approach to environment related management. Most importantly, the toneshould be set at the top. Top management commitment is essential, preferably at the board level.Accordingly, companies should ensure that directors’ skill sets include risk management of social andenvironmental issues. Most importantly, companies should realize that enhanced environmentalperformance can and will lead to improvement in the economic performance of the enterprise.